A Systematic Literature Review on Mathematics Mobile Applications in Education - Gayatiri A/P Balasubramaniam; Murugan A/L Rajoo; Mohd Faizal Nizam Lee Bin Abdullah (Journal of Mathematics and Mathematics Education, 2022)
The usage of mobile applications in today’s teaching and learning system is an active area of research. This study was a Systematic Literature Review (SLR) using the PRISMA model by identifying various appropriate and relevant kinds of literature to identify the usability of mobile applications in education. Data search was carried out using criteria determined by researches from various search engines such as Google Scholar, ERIC, Scopus, Research gate and others as SLR was performed on papers obtained from these databases. In total 77 articles were retrieved; out of which 30 were similar to the purpose of this paper. Out of 30, only 15 articles were relevant to this study. Furthermore, the data were analysed using a qualitative approach to describing the research findings. The results showed that three main research themes have been found, namely the purpose of the study, targeted population and research design. Outline, the analysis results of these articles stated that the implementation of mathematics mobile applications in education is still under consideration in Malaysia. These findings are expected to serve as a foundation for teachers, education observers, and education policymakers at all levels of government, including local, state, and federal governments, as well as the Ministry of Education, to develop policies that support the development of mathematics mobile applications in education. The findings of SLR provided insight into the field's primary contributions, gaps, and chances, which created a conversation about essential research areas in future.